Usability Testing to Improve Research Data Services - Volentine, Rachel; Owens, Amber; Tenopir, Carol; Frame, Mike (Qualitative and Quantitative Methods in Libraries, 2017)
Usability refers to the ease and accessibility of a system.  Usability testing seeks to study how users interact with a system in order to improve the users’ experience and satisfaction in achieving their objectives with the system.  Usability testing is an important metric for improving a library’s online services, including research data services.  Libraries can help make research data available by providing repositories and data curation services for researchers to house their collected data. Providing services throughout the science data life cycle (i.e. plan, collect, share, and preserve) is important for producing higher quality research, expanding its impact, and data reuse.  The Data Observation Network for Earth (DataONE) is supported by the US National Science Foundation and seeks to provide the framework and cyber-infrastructure to meet the needs of the science community to provide constant and secure access to Earth observational data.   The DataONE network has heavily invested and implemented a comprehensive Usability Program to ensure user-centric software and components are made available to the variety of DataONE stakeholders.  DataONE’s ONEMercury is a search tool for scientific data, and the ONEDrive is a mounted workspace on the user’s computer that works with ONEMercury.   In 2012, a usability test was performed of the DataONE’s ONEMercury tool to evaluate how scientists engage with its content and information.  Twenty-six participants performed a series of tasks using the tool. MORAE software recorded the sessions, including screen display, keystrokes, and mouse movements.  Participants were also asked to think aloud as they completed the tasks.  The results were analyzed by observation, think aloud, time on task, and number of errors. Another usability test was performed of the DataONE’s ONEDrive to assess user impressions as the tool was in development.  Six participants were shown a wireframe of the tool and asked for their feedback.  This paper proposes to examine the results from the ONEMercury and ONEDrive tests and draw implications for librariesand other data providers wishing to implement and utilize usability practices and principles.